Impact evaluation: an essential tool to improve FDI promotion - Sandro Zolezzi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
This Perspective explores how impact evaluation on IPA's activities and projects can substantially improve the effectiveness and the competitive position of attracting FDI to the host country.
Keywords: 330